AN ACT RELATING TO SMOKING IN PUBLIC PLACES - BOUCHER,RP; BURNS,RF; CONNORS,HJ; HORAN,RK; KILMARX,MN (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Draft of Rhode Island General Assembly act relating to smoking in public places. Lists places where smoking is to be banned. Discusses enforcement of policies and punishments for not adhering to them.